2020
DOI: 10.1073/pnas.1918950117
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory CD8 T cells that recognize Qa-1 expressed by CD4 T-helper cells inhibit rejection of heart allografts

Abstract: Induction of longstanding immunologic tolerance is essential for survival of transplanted organs and tissues. Despite recent advances in immunosuppression protocols, allograft damage inflicted by antibody specific for donor organs continues to represent a major obstacle to graft survival. Here we report that activation of regulatory CD8 T cells (CD8 Treg) that recognize the Qa-1 class Ib major histocompatibility complex (MHC), a mouse homolog of human leukocyte antigen-E (HLA-E), inhibits antibody-mediated imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…A subset of CD8+ Treg cells recognizes Qa-1, which is essential for the maintenance of self-tolerance (Choi et al, 2020). Qa-1 inhibits NK cells-mediated T-cell killing via suppressing CD8+CD103+ Treg-cells.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of CD8+ Treg cells recognizes Qa-1, which is essential for the maintenance of self-tolerance (Choi et al, 2020). Qa-1 inhibits NK cells-mediated T-cell killing via suppressing CD8+CD103+ Treg-cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to abovementioned EAE model (19,36,37), CD8 + CD122 hi Ly49 + Tregs have documented functions in various settings, including colitis (38,39), hepatitis (40), arthritis (41), diabetes (42,43), viral infection (44), tumor immunity (45), atherogenesis (46) and organ transplantation (47). The best demonstrated role of CD8 + Tregs is to suppress GC reaction.…”
Section: Cd122 Hi Ly49 + Cd8 + Treg -Discovery and Functionmentioning
confidence: 99%
“…Similarly to Qa‐1 −/− mice, Qa‐1 D277K mice develop lupus‐like autoimmune phenotype with tissue‐specific autoantibodies and lymphoid infiltration of peripheral organs [135, 141]. They also show enhanced susceptibility to EAE [141] and faster rejection of allograft associated with an increased production of antibodies specific for the donor organ compared to WT recipients [142]. It has been shown that these effects are dependent on IFN‐γ, perforin, and IL‐15, but not on FasL [135, 141].…”
Section: Qa‐1‐restricted T Cellsmentioning
confidence: 99%
“…Another obstacle is that there is no consensus about how this population can be phenotypically distinguished from other CD8 + T cells. Whereas one study described Qa‐1‐restricted CD8 + T cells as CD44 + CXCR5 + [142], another study characterized Qa‐1‐restricted T cells as CD8 + CD122 + CD44 + Ly49 + , which connects them to the previously described CD8 + CD122 + cells [47]. Importantly, Qa‐1‐restricted CD8 + CD44 + CD122 + Ly49 + Tregs express Helios, a transcription factor essential for the maintenance of their suppressive function [134].…”
Section: Qa‐1‐restricted T Cellsmentioning
confidence: 99%